Prevalence, microbiology, and antimicrobial susceptibility profile of bacterial skin and soft tissue infections in pediatric patients with malignancies at a referral teaching hospital in Shiraz, Iran - Seyed Reza Abdipour Mehrian; Fatemeh Noushadi; Yaser Pourasghar; Armina Farkarian; Elahe Meftah; Fatemeh Homayounifar; Ali Amanati (BMC Infectious Diseases)
Abstract Background and aims Skin and soft tissue infections (SSTIs) in pediatric oncology patients present significant challenges owing to their immunocompromised condition and susceptibility to severe infections. This study aimed to assess the prevalence, microbiology, and antibiotic resistance patterns of SSTIs in children with malignancies admitted to a referral teaching hospital. Methods A total of 227 pediatric patients with cancer were included in this descriptive cross-sectional study. The data collected included demographics, malignancy type, neutropenic status, infection sites, microbial culture results, and clinical outcomes. Bacterial cultures were performed on samples from the blood, wounds, and other infection-related sites. Pathogens were identified using standard microbiological methods, and antibiotic susceptibility was determined using the disk diffusion (Kirby-Bauer) method, following the Clinical and Laboratory Standards Institute (CLSI) guidelines. Results Among the 227 patients, 57.71% were male and 42.29% were female, and the most prevalent age group was 1 to 6 years (39.65%). Hematologic malignancies were observed in 57.33% of the patients, solid tumors in 39.11%, and leukemia was the most common malignancy (40.81%). Bloodstream infections (BSIs) were identified in 7.05% of patients, while a notable proportion of cases (92.95%) were culture-negative, warranting consideration of non-bacterial etiologies or prior antibiotic use. Among the 227 site-specific culture samples, Escherichia coli (36.54%) and Staphylococcus aureus (23.08%) were the most common pathogens. Other frequently isolated bacteria include Pseudomonas aeruginosa, Klebsiella spp., and coagulase-negative Staphylococcus. Antibiotic sensitivity testing revealed that E. coli is sensitive to ampicillin-sulbactam and colistin, whereas S. aureus is sensitive to chloramphenicol and cotrimoxazole. In terms of patient outcomes, > 95% of patients achieved complete recovery, whereas 3.96% had fatal outcomes. Multivariate analysis identified age < 5 years (adjusted odds ratio [aOR] = 8.03, p = 0.004) and perianal abscesses (aOR = 4.4, p = 0.038) as independent risk factors significantly associated with an increased risk of BSI. Male sex was associated with a reduced risk for BSI (aOR = 0.62). Conclusion Our study highlights the significant burden of SSTIs in pediatric oncology patients, with E. coli and S. aureus being the predominant pathogens. Younger age and perianal abscesses were identified as independent risk factors of BSI, emphasizing the need for heightened vigilance in these subgroups. These findings underscore the importance of targeted preventive strategies to improve the outcomes in this high-risk population. However, it is important to acknowledge that this study was conducted at a single center and the high rate of culture-negative results suggests that non-bacterial etiologies or prior antibiotic use may play a significant role. Clinical trial number Not applicable.